Effect of home-based newborn care on neonatal and infant mortality: a cluster randomised trial in India. Issue 9 (24th September 2020) - Rasaily, Reeta; Saxena, NC; Pandey, Sushma; Garg, Bishan S; Swain, Saraswati; Iyengar, Sharad D; Das, Vinita; Sinha, Sheela; Gupta, Subodh; Sinha, Anju; Kumar, Shiv; Pandey, Arvind; et al.
Abstract : Background: Home-based newborn care has been found to reduce neonatal mortality in rural areas. Study evaluated effectiveness of home-based care delivered by specially recruited newborn care workers- Shishu Rakshak (SR) and existing workers- anganwadi workers (AWW) in reducing neonatal and infant mortality rates. Methods: This three-arm, community-based, cluster randomised trial was conducted in five districts in India. Intervention package consisted of pregnancy surveillance, health education, care at birth, care of normal/low birthweight neonates, identification and treatment of sick neonates and young infants using oral and injectable antibiotics and community mobilisation. The package was similar in both intervention arms—SR and AWW; difference being healthcare provider. The control arm received routine health services from the existing health system. Primary outcomes were neonatal and young infant mortality rates at 'endline' period (2008–2009) assessed by an independent team from January to April 2010 in the study clusters. Findings: A total of 6623, 6852 and 5898 births occurred in the SR, AWW and control arms, respectively, during the endline period; the proportion of facility births were 69.0%, 64.4% and 70.6% in the three arms. Baseline mortality rates were comparable in three arms. During the endline period, the risk of neonatal mortality was 25% lower in the SR arm (adjusted OR 0.75, 95% CI 0.57 to 0.99); the risks of early neonatal mortality, young infant mortality and infant mortality were also lower by 32%, 27%, and 33%, respectively. The risks of neonatal, early neonatal, young infant, infant mortality in the AWW arm were not different from that of the control arm. Interpretation: Home-based care is effective in reducing neonatal and infant mortality rates, when delivered by a dedicated worker, even in settings with high rates of facility births. Trial registration number: The study was registered with Clinical Trial Registry of India (CTRI/2011/12/002181).